2011
DOI: 10.1108/13683041111184062
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management and value creation in service firms

Abstract: Purpose -The purpose of this paper is to analyse the effect of knowledge management (KM) on value creation in Icelandic service firms. The aim is to examine how KM contributes to value creation, and measure the ways in which KM affects intangible assets, such as customer capital, innovation, and human capital.Design/methodology/approach -The authors propose a survey approach conducted in 2007 among 222 firms (46.1 percent response rate). Of these firms 97 had KM programmes in place and this paper is based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 21 publications
(43 reference statements)
2
30
0
2
Order By: Relevance
“…Service providers can create programs to allow tourists to become more physically and emotionally engaged, thus encouraging co-creation of an experience. Service providers should communicate to tourists the message that tourists' ideas are sought and welcomed (Edvardsson & Oskarsson, 2011). In order for a hospitality company to partake in the co-creation process they should clearly understand their role and be able to use the co-creation process effectively and efficiently in order to create financial value in the end.…”
Section: Discussionmentioning
confidence: 99%
“…Service providers can create programs to allow tourists to become more physically and emotionally engaged, thus encouraging co-creation of an experience. Service providers should communicate to tourists the message that tourists' ideas are sought and welcomed (Edvardsson & Oskarsson, 2011). In order for a hospitality company to partake in the co-creation process they should clearly understand their role and be able to use the co-creation process effectively and efficiently in order to create financial value in the end.…”
Section: Discussionmentioning
confidence: 99%
“…It was also embedded in the DNA of the organizations of the biotechnology industry, since R&D activities are at their core processes. Previous studies have indicated that knowledge management facilitates value creation and develops intangible assets of companies [72]. The present study aimed to see if value creation strategies lead to the development of intellectual capital, as well as to more intense knowledge transfers.…”
Section: Intellectual Capitalmentioning
confidence: 91%
“…In the continuation of the theory of resources, comes the knowledge-based approach (KBV) which considers organizational knowledge as a strategic resource determining the competitive advantage of the company. Thus, this theory placed knowledge at the center of the process of creating competitive advantage and value creation (Dubois & Dupuy, 2007). In the same line of idea, Nonaka (2000) describes: "in an economy where the only certainty is uncertainty; the only source of sustainable competitive advantage is knowledge".…”
Section: The Knowledge Managementmentioning
confidence: 99%